EFFORTS TO RECOVER ASSETS FROM CORRUPTION CRIMES THROUGH OPTIMIZATION OF LEGISLATION IN INDONESIA AND A REVIEW OF THE DRAFT LAW ON ASSET FORFEITURE - Irwan Triadi; Bayu Giri Atmojo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Corruption, as an organized and transnational crime, demands a more effective asset recovery mechanism than the conventional criminal approach currently applied in Indonesia. The limitations of criminal law instruments in tracing, confiscating, and repatriating assets that have been transferred, concealed, or placed outside national jurisdiction form the central background for the urgency of the Asset Forfeiture Bill. This study aims to analyze the concept of asset forfeiture for corruption cases through the non-conviction based forfeiture mechanism and assess the alignment of the Asset Forfeiture Bill with international standards, particularly the UNCAC. The research employs a normative legal method through an examination of legislation, academic literature, international documents, and comparative best practices. The findings indicate that the Bill introduces a new enforcement paradigm through in rem procedures, an integrated asset-tracing system, civil judicial control, and transparent asset management. The discussion reveals that although the Bill has significant potential to enhance state asset recovery, its implementation requires strengthened evidentiary standards, protection of property rights, and improved inter-agency coordination. The study concludes that the Asset Forfeiture Bill represents a strategic instrument for improving the effectiveness of anti-corruption efforts, yet its success depends on procedural safeguards, transparency in asset administration, and the institutional capacity of law enforcement bodies.